2010
DOI: 10.1073/pnas.1010631107
|View full text |Cite
|
Sign up to set email alerts
|

Postdetonation nuclear debris for attribution

Abstract: On the morning of July 16, 1945, the first atomic bomb was exploded in New Mexico on the White Sands Proving Ground. The device was a plutonium implosion device similar to the device that destroyed Nagasaki, Japan, on August 9 of that same year. Recently, with the enactment of US public law 111-140, the “Nuclear Forensics and Attribution Act,” scientists in the government and academia have been able, in earnest, to consider what type of forensic-style information may be obtained after a nuclear detonation. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 5 publications
3
75
0
Order By: Relevance
“…Quartz is the only mineral present in both cases, and the peak intensities are similar, suggesting a comparable degree of amorphousness 3 . These results are consistent with previous studies of trinitite 15,16,12,17 and other types of nuclear melt glass.…”
Section: Representative Resultssupporting
confidence: 83%
“…Quartz is the only mineral present in both cases, and the peak intensities are similar, suggesting a comparable degree of amorphousness 3 . These results are consistent with previous studies of trinitite 15,16,12,17 and other types of nuclear melt glass.…”
Section: Representative Resultssupporting
confidence: 83%
“…Both of these effects would increase the final fraction of Fe(II) in the melt glass, and they must be disentangled in order to draw quantitative conclusions regarding the sources of iron in the melt glass. Spectromicroscopic data may provide more detailed information in this regard, as lectron microscopy studies have observed metal-rich regions with dimensions ranging from nanometers to millimeters in Trinity event debris [19,74]. In addition, from the point of view of environmental transport, the presence of a large fraction of U(VI) in a uranyl-like bonding environment is quite interesting, since U(VI) as uranyl is the most soluble and mobile oxidation state of uranium [26,65,[75][76][77].…”
Section: To Fe(iii) and Corresponding U(vi) Reduction To U(iv) It Imentioning
confidence: 99%
“…An understanding of the specific melt glass forms produced by underground and near-surface weapons testing is important for prediction and remediation of contaminant plumes at sites where nuclear testing has occurred. In addition, melt glass can retain a record of chemical signatures of the detonation, including residual actinides from the device [19,20]. For example, studies have shown that analyses of fission product relationships can be useful to constrain the chemical fractionation processes in fallout, and are characteristic of the nuclear event [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Cold War era research focused on the distribution and dispersion of radioactive fallout particulates, these studies are typically motivated by renewed interest in interpreting details and signatures of a device having a potentially unknown origin [43,44,45,46]. For example, a study of trinitite (fallout formed in the Trinity explosion) published in 2006 measured several activation products and fission products via gamma spectroscopy in the glass, from which device characteristics were hypothesized [43].…”
Section: Contemporary Fallout Researchmentioning
confidence: 99%